Utility, publicity, and law : essays on Bentham's moral and legal philosophy - Postema, Gerald J. (Oxford : Oxford University Press, 2019)
The essays in this volume offer a reassessment of Jeremy Bentham's strikingly original legal philosophy. Early on, Bentham discovered his 'genius for legislation' - 'legislation' included not only lawmaking and code writing, but also political and social institution building and engineering of public spaces for effective control of the exercise of political power. In his general philosophical work, Bentham sought to articulate a public philosophy to guide and direct all of his 'legislative' efforts.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 30, 2019).
Keywords: Bentham, Jeremy, -- 1748-1832.; Law -- Philosophy